Simulating damage onset and evolution in fully bio-resorbable composite under three-point bending - Gao, Xi; Chen, Menghao; Yang, Xiaogang; Harper, Lee; Ahmed, Ifty; Lu, Jiawa (Elsevier, 2018)
This paper presents a strain-based damage model to predict the stress-strain relationship and investigate the damage onset and evolution of the fibre and matrix of a fully bio-resorbable phosphate glass fibre reinforced composite under three-point bending. The flexural properties of the composite are crucial, particularly when it is employed as implant for long bone fracture. In the model, the 3D case of the strain and stress was used and the response of the undamaged material was assumed to be linearly elastic. The onset of damage was indicated by two damage variables for the fibre and matrix, respectively. The damage evolution law was based on the damage variable and the facture energy of the fibre and matrix, individually. A finite element (FE) model was created to implement the constitutive model and conduct numerical tests. An auto-adaptive algorithm is integrated in the FE model to improve the convergence. The FE model was capable of predicting the flexural modulus with around 3% relative error, and the flexural strength within 2% relative error in comparison with the experimental data. The numerical indices showed that the top surface of the sample was the most vulnerable under three-point bending. It was also found that the damage initiated in the fibre, was the primary driver for composite failure under three-point bending.